Detection of natural autoimmunity to ghrelin in diabetes mellitus - Kasim, Rega H.; Chillon, Thilo Samson; Eleftheriadou, Anna Maria; Rijntjes, Eddy; Minich, Waldemar B.; Zechmann, Stefan; Schomburg, Lutz (Frontiers in Medical Technology, 2024)
Objective Ghrelin is an orexigenic peptide that becomes post-translationally modified. Natural autoantibodies to ghrelin (ghrelin-aAb) have been described in healthy subjects, in eating disorders and rheumatic diseases, with potential clinical relevance. Despite these important reports, the data base on the prevalence and physiological role is small and technical approaches for assessing ghrelin-aAb are few, encouraging respective research for improving knowledge on the potential endocrine significance. Methods A novel immunoprecipitation assay was generated based on a fusion protein of human ghrelin with a reporter gene. Assay quality was verified with commercial antibodies. Assay characteristics and matrix effects were determined, including stability of natural ghrelin-aAb to freezing, signal linearity in dilution experiments, and comparison of different matrices. Three groups of serum samples were analyzed for ghrelin-aAb, comprising commercial sera from healthy subjects and patients with type 1 or type 2 diabetes mellitus. Results The newly generated ghrelin-aAb assay proved sensitive, robust and reliable over a broad concentration range. Results from serum and plasma differed slightly. The signals from serum remained stable towards freezing and thawing, and in dilution experiments. Applying a mathematical criterion for outliers (P75 + 1.5-times IQR), an average prevalence of 11%–12% of positive samples was identified in the different human cohorts, with no significant sex-or disease-related difference. General significance A novel diagnostic autoantibody assay detected ghrelin-aAb with a similar prevalence in diabetic patients and controls, suggesting that autoimmunity to ghrelin plays little role in diabetes mellitus, but may be of relevance in other diseases where ghrelin signaling is essential.